(untitled) (Conference Zone, 2022)
This article’s goal is to briefly describe the significance, setting, duration, impetus, and rationale behind the establishment of international foreign language certifications. There are standardized tests that measure the proficiency in foreign languages that are spoken on a global scale. Successful exam takers will receive official certificates. Each certificate, in turn, has unique advantages. For instance, a TESOL certificate holder can instruct English in any nation. There are other prerequisites and possibilities for other language certificates that are similar. For a variety of reasons, foreign language certificates can be earned. Some take the test in order to work or reside in that nation, while others do so in order to enroll in one of its colleges.